Znaczenie wiedzy w małych i średnich przedsiębiorstwach - Jakubowska, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The process of development and preparing a company for the 21st century is becoming more and more independent from an economic situation in which the company exists. Growing complexity and changeability of environment enforces companies to re-define the business, change products and processes all the time. The third millennium brought changes in all fields of activity. Companies must know how to manage in a new era - the era of information, knowledge, and data exchange. In consequence, the role of knowledge, creation and non-material resources in economy and business is growing. The author states that companies have to understand the importance of knowledge and learn how to manage this resource. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 154-164